`Hand, foot, and mouth disease' associated with Coxsackie A5 virus. Issue 1 (January 1963) - Flewett, T. H.; Warin, R. P.; Clarke, Suzanne K. R.
Abstract : Seven cases are described of highly infectious disease characterized by vesicular eruptions in the mouth and on the hands and feet. In previous outbreaks described in the literature Coxsackie type A16 virus was isolated but from these cases, similar clinically, Coxsackie type A5 virus was isolated.